Revealing the impact of ChatGPT towards students' writing skill: ChatGPT as a tool - Mohammad Abdul Kafi; Him'mawan Adi Nugroho; Slamet Setiawan (Electronic Journal of Education, Social Economics and Technology, 2026)
Writing is a fundamental skill in English as a Foreign Language (EFL) education, yet it presents challenges that require high levels of cognitive and linguistic proficiency. This study investigates the impact of ChatGPT, an AI-powered writing tool, on the writing skills and perceptions of university-level EFL students. Therefore, this study focuses on students' experience of using ChatGPT for writing and their perception. Using a mixed-methods approach, data were collected from 33 participants across multiple universities. The findings reveal that ChatGPT significantly enhances students' writing abilities in areas such as grammar, vocabulary, and content organization, while also reducing anxiety and increasing confidence during the writing process. Students praised ChatGPT for its accessibility, efficiency, and ability to generate ideas, yet acknowledged its limitations in accuracy, pronoun placement, and punctuation. These results align with existing theories on technology acceptance and AI’s role in education, emphasizing ChatGPT’s potential as a supportive tool rather than a standalone solution. The study concludes with recommendations for balancing AI use with critical thinking and human oversight to foster independent learning and sustainable writing development.